2003
DOI: 10.1021/ja034221r
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A Forms a Carbon-Bonded C8-Deoxyguanosine Nucleoside Adduct:  Implications for C8 Reactivity by a Phenolic Radical

Abstract: The ability of the carcinogenic fungal toxin Ochratoxin A (OTA, 1) to react with deoxyguanosine (dG) has been assessed using electrospray mass spectrometry and NMR. Photoexcitation of OTA (100 muM) in the presence of 50 mol equiv of dG led to the isolation and identification of the C8-deoxyguanosine nucleoside adduct 4. Importantly, the same adduct was formed upon oxidative activation of OTA using horseradish peroxidase (HRP)/H2O2 or the transition metals Fe(II) and Cu(II), as evidenced by mass spectrometry. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(146 citation statements)
references
References 23 publications
7
139
0
Order By: Relevance
“…The OTB-GSH or OTB-NAC conjugates are generated photochemically from displacement of the C5-Cl atom of OTA by the sulphur atom of GSH or NAC. The electrophilic intermediate in this reaction also reacts with dG to yield the OTB-dG adduct (21), which has been detected by LC-MS in the kidney of male rats fed a carcinogenic dose of OTA (22). Thus, OTB-GSH and OTHQ-GSH, along with the corresponding NACconjugates, were considered as appropriate biomarkers for OTA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The OTB-GSH or OTB-NAC conjugates are generated photochemically from displacement of the C5-Cl atom of OTA by the sulphur atom of GSH or NAC. The electrophilic intermediate in this reaction also reacts with dG to yield the OTB-dG adduct (21), which has been detected by LC-MS in the kidney of male rats fed a carcinogenic dose of OTA (22). Thus, OTB-GSH and OTHQ-GSH, along with the corresponding NACconjugates, were considered as appropriate biomarkers for OTA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ochratoxin A at the level of cellular metabolism affects the enzymes connected with the metabolism of phenylalanine and causes the inhibition of the mitochondrial synthesis of ATP [17] and acceleration of the peroxidation of lipids [18]. Due to the constitution of ochratoxin A (halogen derivative of phenol), the action of this mycotoxin may also result in the modification of bases constituting the nucleic acids, which may cause mutations and contribute to the development of carcinogenic diseases in the organisms exposed to its influence [19].…”
Section: Ochratoxinmentioning
confidence: 99%
“…As the 32 P-postlabeling method cannot distinguish between adducts caused by the chemical itself and those caused by the products of oxidative stress and cytotoxicity, the validity of using the 32 P-postlabeling method for determining DNA adducts and, moreover, the interpretation of results obtained using this method as representing a purely genotoxic mechanism of action must be questioned. Furthermore, neither the presence of oxidative changes, nor the reported DNA adducts could be corroborated using HPLC-MS or LC-MS. 115,116,122 Dai and coworkers 123 recently reported that OTA can indeed react with DNA via a phenolic radical, and have synthesized and characterized the resulting C8-deoxyguanosine (dG) adduct. The same group previously described the formation of a quinone species resulting from the dechlorination of OTA.…”
Section: Is Ota (Or One Of Its Metabolites) Genotoxic?mentioning
confidence: 99%